ISNS General Guidelines for Neonatal Bloodspot Screening 2025 - Dianne Webster; Amy Gaviglio; Aysha Habib Khan; Mei Baker; David Cheillan; Layachi Chabraoui; Ghassan Abdoh; Juan Cabello; Roberto Giugliani; Dimitris Platis; Jan Østrup; R. Rodney Howell; et al. (International Journal of Neonatal Screening)
Part of the vision of the ISNS is ‘to enhance the quality of neonatal screening and medical services through dissemination of information, guidelines and best practices.’ Although newborn screening encompasses testing in the newborn period for critical congenital heart disease, hearing impairment, birth defects, and congenital biochemical disorders (usually on bloodspots), this guideline is specifically about bloodspot screening. The ISNS has provided neonatal screening guidelines for many years and here presents the renewed 2025 General Guidelines for Neonatal Bloodspot Screening. They are intended to provide a framework for screening programs to develop specific policies around all aspects of the newborn screening system, offering the basic set of items for consideration. These guidelines provide trusted anchors to build, expand, or maintain robustly organized neonatal or newborn screening (NBS) programs and a checklist to evaluate and improve the essential elements of those programs. For starting or developing programs, it is a set of elements for which provisions need to be in place and a checklist of items that the screening program should at a minimum have provisions for. The publication of these guidelines is meant as a starting point for interactive discussion, to further improve this document and expand where necessary.